STUDI PAPARAN MEDAN MAGNET SALURAN UDARA TEGANGAN EKSTRA TINGGI (SUTET) PADA PERTUMBUHAN SAYURAN CAISIM (BRASSICA JUNCEA L) - Sri Budarsa, I Gede Ketut; Sandi Adnyana, I W; Mahardika, I G. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 4 No 2, 2012)
The existence of 500 kv extra high voltage transmission lines causes some area of villager’s farms to be under the transmission lines, so the research is urgently needed to see how the exposure of magnetic fields of 500 kv extra high voltage transmission lines influences the growth of plants. The aim of this research main function is to know the growth response of green mustard with the exposure to the extra high voltage magnetic field. Observation is focused on the area of leaf, amount of chlorophyll, weight of dry leaf, and net assimilation rate .The research applies completely randomized design repeated 3 times and 4 kinds of treatments with the different exposure of magnetic field. The data are quantitatively analyzed using analysis of variant method. The result of this research shows that the exposure of magnetic field influences the reduction of green mustard leaf, amount of leaf chlorophyll, net assimilation rate and the dry weight of green mustard leaf. Based on the result of the research it can be concluded that the exposure of magnetic field can reduce the growth of green mustard witch are under 500 kv extra high voltage transmission lines
Keywords: extra high voltage transmission lines, exposure of magnetic field, growth of mustard green.